An Unusual Cardiac Cause of Unilateral Neonatal Wheezing - James Brock; Eliezer Nussbaum; Jared Shows; Son Nguyen; Shaun P. Setty (Hindawi Limited, 2019)
A neonate presented three days after birth with left-sided unilateral inspiratory wheezing, intermittent respiratory distress, and desaturations. She was found to have a large ductus arteriosus aneurysm that caused compression of her left mainstem bronchus and left pulmonary artery. This lesion was not identified prior to birth on routine prenatal screening, which included fetal ultrasonography. Diagnosis was made on day of life (DOL) 5 by a computed tomography with angiography scan. On DOL 7, she underwent cardiac surgery which included resection of the ductal aneurysm, patch reconstruction of the transverse aortic arch and descending aorta, patent ductus arteriosus excision, and atrial secundum septal defect repair. There were no postoperative complications, and she has been asymptomatic since.